Comparison of the fire resistance behaviour of structural insulated panels with expanded polystyrene core treated with intumescent coating (2021)
It is necessary to study fire safety in buildings because the lack of knowledge in the behavior of materials has taken too many lives. However, this field has designed innovating construction systems and materials such as structural insulated panels (SIP), this is a much more practical alternative for fastest constructions, reducing the amount of material waste, offering cleaner and lighter works, its thermal insulation properties in possible fires and better durability in construction in the account of the various internal compositions. The objective of this article is to evaluate and analyze the fire resistance of two SIP for dividing and structural walls, made up of a core of expanded polystyrene (EPS) with dimensions of 3150x3000mm, one covered with cement board and the other one covered with gypsum plasterboard, both are treated with intumescent paint. The samples were exposed to the fire curve based on the ISO 834: 2014 standard and then analyzed and compared with each other. The obtained results indicate the incorporation of gypsum plasterboards provides a gain of 45 min of resistance to fire, compared to the system it only contains cement board, positively influencing gypsum in the stability and property of the thermal insulation of the panels. Likewise, it was found that intumescent coatings application effectively helps to give the SIP greater protection against fire.